LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK DISKUSI UNTUK MENINGKATKAN KEMATANGAN KARIR SISWA KELAS XC SMA VIRGO FIDELIS BAWEN - Cahya Novela Riwanti, Mutiara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study was conducted at Virgo Fidelis Bawen High School using a Pre-Experimental Design with a one-group pre-test and post-test format. The research population consisted of 34 students from class XC, from which 8 students in the low category were selected as samples. The study employed group guidance and group discussion techniques, with data collection based on a career maturity scale following Super's theory. The purpose of the research was to assess the significance of improvement in students' career maturity after receiving group guidance services through group discussion techniques. Data analysis was performed using the Paired Sample T-Test. The analysis results revealed a calculated t value of -10.453 with a significance value (p) of 0.00, indicating a significant improvement in the career maturity of students after receiving the group guidance services using group discussion techniques.